Effect of Instagram Post on Legitimacy and Reputation of Indonesian National Police - Tyan Ludiana Prabowo (Universitas Multimedia Nusantara, 2021)
Indonesia is rated 60th out of 61 countries in terms of reading interest. It is reasonable to predict that message penetration to the Indonesian people will be more straightforward in the form of images, visuals, or memes based on this basic data. Suppose it is to be used as an official media platform to build the legitimacy and reputation of the police. In that case, the market niche for Indonesian Instagram users is also quite vast and capable. This study intends to explain the relationship (correlation) between variables, especially posting variables with legitimacy and reputation variables on Instagram @Divisihumaspolri. The research method used in this study is content analysis on Instagram @Divisihumaspolri from January 1, 2018, to June 31, 2018. The conclusions in this study indicate an influence between posting to the Instagram account @Divisihumaspolri on the legitimacy and reputation of the Indonesian National Police organization because the coefficient of the relationship is positive. This means that legitimacy is positively and significantly related to reputation. Thus, the post of @Divisihumaspolri affects legitimacy variables, including regulations, norms, cultural knowledge, and reputation variables, including credibility, reliability, trustworthiness, and responsibility. Keywords: Instagram, Post, Legitimacy, Reputation, Indonesian National Police